A fast high-order algorithm for the multiple cavity scattering. Issue 1 (2nd January 2019) - Zhao, Meiling; An, Sheng; Nie, Yufeng
ABSTRACT: A fast high-order algorithm is proposed for solving the electromagnetic scattering from multiple cavities embedded in an infinite ground plane. By means of a transparent boundary condition, we transform the multiple cavity scattering problem into the Helmholtz equations restricted to each cavity with coupled nonlocal boundary conditions on the apertures. Then a fourth-order method in each cavity is constructed. It results in a big system involving the Helmholtz equations with the coupled transparent boundary conditions, which is further reduced to a small system that includes only the coupling of the aperture system of each cavity. The cost of calculating the radar cross section isO ( N   M l o g ( n M ) ) withN × M meshes in each cavity, where n is the number of separate cavities. Numerical experiments with large wave numbers are presented to verify the efficiency of the proposed method.